Diurnal and menstrual cycles in body temperature are regulated differently: A 28-day ambulatory study in healthy women with thermal discomfort of cold extremities and controls. (February 2014) - Kräuchi, Kurt; Konieczka, Katarzyna; Roescheisen-Weich, Corina; Gompper, Britta; Hauenstein, Daniela; Schoetzau, Andreas; Fraenkl, Stephan; Flammer, Josef
<x xml:space="preserve">Abstract</x> Diurnal cycle variations in body-heat loss and heat production, and their resulting core body temperature (CBT), are relatively well investigated; however, little is known about their variations across the menstrual cycle under ambulatory conditions. The main purpose of this study was to determine whether menstrual cycle variations in distal and proximal skin temperatures exhibit similar patterns to those of diurnal variations, with lower internal heat conductance when CBT is high, i.e. during the luteal phase. Furthermore, we tested these relationships in two groups of women, with and without thermal discomfort of cold extremities (TDCE). In total, 19 healthy eumenorrheic women with regular menstrual cycles (28–32 days), 9 with habitual TDCE (ages 29 ± 1.5 year; BMI 20.1 ± 0.4) and 10 controls without these symptoms (CON: aged 27 ± 0.8 year; BMI 22.7 ± 0.6; p < 0.004 different to TDCE) took part in the study. Twenty-eight days continuous ambulatory skin temperature measurements of distal (mean of hands and feet) and proximal (mean of sternum and infraclavicular regions) skin regions, thighs, and calves were carried out under real-life, ambulatory conditions (i-Buttons® skin probes, sampling rate: 2.5 min). The distal minus proximal skin temperature gradient (DPG) provided a valuable measure for heat redistribution from the core to the shell, and, hence, for internal heat conduction. Additionally, basal body temperature was measured sublingually directly after waking up in bed. Mean diurnal amplitudes in skin temperatures increased from proximal to distal skin regions and the 24-h mean values were inversely related. TDCE compared to CON showed significantly lower hand skin temperatures and DPG during daytime. However, menstrual cycle phase did not modify these diurnal patterns, indicating that menstrual and diurnal cycle variations in skin temperatures reveal additive effects. Most striking was the finding that all measured skin temperatures, together with basal body temperature, revealed a similar menstrual cycle variation (independent of BMI), with highest and lowest values during the luteal and follicular phases, respectively. These findings lead to the conclusion that in contrast to diurnal cycle, variations in CBT variation across the menstrual cycle cannot be explained by changes in internal heat conduction under ambulatory conditions. Although no measurements of metabolic heat production were carried out increased metabolic heat generation during the luteal phase seems to be the most plausible explanation for similar body temperature increases.